xCT, not just an amino-acid transporter: a multi-functional regulator of microbial infection and associated diseases - Dai, Lu; Noverr, Mairi C.; Parsons, Chris; Kaleeba, Johnan A. R.; Qin, Zhiqiang (Frontiers in Microbiology, 2015)
Expression of xCT, a component of the xc− amino-acid transporter, is essential for the uptake of cystine required for intracellular glutathione (GSH) synthesis and maintenance of the intracellular redox balance. Therefore, xCT plays an important role not only in the survival of somatic and immune cells, but also in other aspects of tumorigenesis including the growth and malignant progression of cancer cells, resistance to anticancer drugs, and protection of normal cells against oxidative damage induced by carcinogens. xCT also functions as a factor required for infection by Kaposi's sarcoma–associated herpesvirus (KSHV), the causative agent of Kaposi's sarcoma (KS) and other lymphoproliferative diseases associated with HIV/AIDS. In spite of these advances, however, our understanding of the role of xCT in the pathogenesis of infectious diseases is still limited. Therefore, this review will summarize recent findings about the functions of xCT in diseases associated with microbial (bacterial or viral) infections, in particular KSHV-associated malignancies. We will also discuss the remaining questions, future directions, as well as evidences that support the potential benefits of exploring system xc− as a target for prevention and clinical management of microbial diseases and cancer.